2014
DOI: 10.1016/j.jclinane.2014.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Elective change of surgeon during the OR day has an operationally negligible impact on turnover time

Abstract: Study Objective To compare turnover times for a series of elective cases with surgeons following themselves to turnover times for a series of previously scheduled, elective procedures where the following surgeon differed from the preceding surgeon. We also considered the effect of changing procedure types and the time of day on turnover time. Design Retrospective, cohort study. Setting University-affiliated teaching hospital. Measurements We used the operating room statistical database to gather 32 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 22 publications
0
26
0
1
Order By: Relevance
“…4,7 However, Austin et al determined that a change in surgeon had a negligible effect on OR turnover time. 9 Despite evidence that these individuals hold much of the responsibility for procedural efficiency, Masursky et al previously found that surgeons were biased when it came to planning OR turnaround times. 11,13 Correcting discrepancies between planned and actual OR turnaround times can reduce patient wait times, potentially enabling more procedures to be performed in a single OR, especially when numerous short surgeries are scheduled.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,7 However, Austin et al determined that a change in surgeon had a negligible effect on OR turnover time. 9 Despite evidence that these individuals hold much of the responsibility for procedural efficiency, Masursky et al previously found that surgeons were biased when it came to planning OR turnaround times. 11,13 Correcting discrepancies between planned and actual OR turnaround times can reduce patient wait times, potentially enabling more procedures to be performed in a single OR, especially when numerous short surgeries are scheduled.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,7,8 In contrast, a change in surgeon has been found to have no significant impact on OR efficiency. 9 In an in-depth analysis of OR data, including causes of delays and personal accountability, Overdyk et al found that teamwork improved OR efficiency. 10 However, Masursky et al observed that both surgeons and, to a lesser extent, anaesthesiologists, judged OR turnaround times according to mental models of factors influencing turnover; thus, the perceptions of surgeons or anaesthesiologists should not be relied upon to make OR management decisions.…”
mentioning
confidence: 99%
“…Statistical analyses are commonly done after batching (binning) the data into 4-week periods, because managerial covariates are often unmeasured, not only nationwide but at individual hospitals (e.g., staff schedules and correlations among patients caused by appropriate queue management based on threshold numbers of patients). [11][12][13][14][15][16][17][18][19][20] For example, we used the Kruskal-Wallis test to compare the labor epidural durations among the 7 days of the week. At random, 1.0% of the 175 hospitals should be statistically significant at a P < 0.01 criterion, but 10.6% www.anesthesia-analgesia.org…”
Section: Statistical Explorations and Intermediate Resultsmentioning
confidence: 99%
“…(11)(12)(13) OR scheduling covers two different levels: monthly staff scheduling and daily allocation scheduling (daily staff assignment). (14) By definition, the former refers to long-term scheduling, whereas the latter refers to day-to-day function. Staff scheduling is the process of deciding which staff is available on a given day for a given shift.…”
Section: Planned Schedulingmentioning
confidence: 99%